Robust Single Machine Scheduling with Stochastic Processing Times Based on Event Point - Yao, Chun; He, Xiao Xia; Tang, Qiu Hua (Applied Mechanics and Materials, 2014)
The scheduling of the single machine is of major importance in applications. The focus of this work is to analyze the scheduling problems in single-machine scheduling in the presence of uncertain parameters. By assuming that the processing time is represented by the nominal value plus a perturbation, we propose a robust model base on event point, and we obtain the feasible job sequence with some probability confidence level.